Roussouly type 2 could evolve into type 1 shape as sagittal spinal alignment deterioration progresses with age - Sun, Wenzhi; Li, Yongjin; Chen, Xiaolong; Wang, Baobao; Kong, Chao; Wang, Peng; Lu, Shibao (Frontiers in Surgery, 2022)
Study Design: Cross-sectional study. Objective: To identify whether Roussouly type 2 could evolve into type 1 as the deterioration progresses. Methods: The sagittal parameters of all subjects were measured: T1 pelvic angle (TPA), lumbar lordosis (LL), PI, pelvic tilt (PT), L4–S1 angle, thoracolumbar kyphosis (TLK), thoracic kyphosis (TK), lumbar sagittal apex (LSA), lordosis distribution index (LDI) and number of vertebrae included in the lordosis (NVL). All subjects were distributed into two groups; with primary (de novo) degenerative scoliosis (PDS) and without PDS. Subjects without PDS were divided into young adult, adult, middle-aged and elderly groups. The differences in sagittal parameters of each subgroup were compared. Results: In total, 270 subjects were included with a mean age of 58.6 years (range 20–87 years). There was a stepwise increase in the proportion of type 1 with age, whereas type 2 decreased. The TPA, PT, PI-LL, TK, TLK and LDI increased with age in subjects without PDS. The TPA, LDI, TLK and TK increased with age in subjects who displayed type 1, whereas the PT, LL, L4–S1 and PI-LL were unchanged. The TPA, PT, PI-LL and TLK increased with age in subjects who displayed type 2, whereas LL and L4-S1 were decreased, while the LDI and TK remained unchanged. The LSA of subjects without PDS became lower and the NVL decreased with age, with similar phenomena found in the subjects with type 2. There was no statistical difference among the groups for the LSA or NVL distribution of subjects with type 1. The TPA, PT and PI-LL of subjects with PDS were greater than those in Group IV, while the SS, LL and TK were less. The Roussouly-type, NVL and LSA distribution were identical between these two groups. Conclusion: Roussouly type 1 shape may not be an actual individual specific spine type. Rather, type 2 could evolve into the “type 1” shape as deterioration of the sagittal spinal alignment progresses with age. Primary (de novo) degenerative scoliosis had little effect on whether type 2 became type 1. This should be taken into consideration during the assessment and restoration of sagittal balance.